Spatial Analysis of Erosion Danger Level at Rambut Watershed Area Tegal District - Totok Wiji Sugiarto; Dyah Ari Wulandari; Pratono Samto Atmojo (Journal of Development Research, 2020)
Erosion is a series of sedimentation processes associated with weathering, releasing, transporting, and settling grains of earth or earth's crust. As a watershed, watersheds are very vulnerable to erosion and sedimentation problems. This research was aimed to predict the erosion danger level at Rambut Watershed Area based on the Universal Soil Loss Equation Formula, by applying a Geographical Information System analysis. Based on the formula, we used four types of maps, i.e. rainfall, soil, slope, and land cover map. On each map, classification was done to get four to five classes based on a specific factor standard. To get the final result from the erosion danger levels which is categorized into five classes, they are very light, light, moderate, heavy, and very heavy, it is necessary to overlay the four types of maps. The results showed that the erosion danger levels at Rambut watershed area ranged from very light to very heavy, with the percentages of the affected areas are 46.91%; 35.13%; 12.47%; 3.67%; and 1.82% respectively. The very heavy and heavy danger areas covered 356.02 ha. And 717.99 ha. respectively. The results are used as a database to make a good planning watershed area management. Keywords: Erosion, GIS, overlay, USLE, watershed management, weathering